Hospital noise and patients' wellbeing - Cunha, Madalena (2015)
Abstract: Noise can produce an undesired physiological or psychological response in an individual and it has implications in chronic mental and physical health. This study´s purpose was to confirm the relationship between hospital noise and patients´ wellbeing, trough a descriptive design. It was performed in 84 patients (59.5 % male and 40.5 % female) admitted in three medical/surgical care units of a Portuguese hospital (CHBV, EPE). The questionnaire was composed by three parts: one regarding to socio-demographic and clinical data, other assessing the patient´s noise perception - the Environmental Comfort Questionnaire from Cunha and Silva (2012) - and the Positive and Negative Affect Schedule (PANAS) by Watson, Clark and Tellegen (1988), Portuguese version from Galinha and Pais-Ribeiro (2005). The results showed that: Clinical Sources of Noise (r=-0269, p=0.013), the Sum Score of the Environmental Comfort (r=- 0254, p=0.020) and physiological and psychological effects caused by noise (r=-0362, p=0.001) are statistically significant related with patients´ subjective wellbeing. It is confirmed that subjective wellbeing is influenced by the hospital noise in general and, more specifically, the noise from clinical sources (e.g. monitors, infusion pumps and other equipments). It is also confirmed that some physiological and psychological disturbances in patients are related to hospital noise. Facing the results, it is imperative to promote the wellbeing of admitted patients by lowering the noise levels.